La violencia de género en Ecuador: : El gobierno de Lasso en deuda con las mujeres - Pacheco Lupercio, Fernanda (2023)
This article aims to analyze the current situation of gender violence in Ecuador. Understanding that it is a tool of social control over the bodies of women and girls, which seeks to ensure the reproduction of the current social order. The year 2022 has been the cruelest for women, there are 272 victims of femicide; that is, patriarchal violence claims a life every 28 hours. Faced with this reality, the plural feminist movement is mobilized to demand effective measures for the prevention and eradication of gender violence. The exponential increase in violence against women coincides with the first 18 months of Guillermo Lasso's government, showing that public policies to ensure women a life free of violence are insufficient given the seriousness of the problem.